2023
DOI: 10.1002/gps.5895
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics, life problems and clinical management of older adults who self‐harm: Findings from the multicentre study of self‐harm in England

Abstract: Background Older adults have a high risk of suicide following self‐harm. Contemporary information on self‐harm in this population is needed to inform care provision. Objectives To examine subgroup differences in the incidence of self‐harm, sociodemographic and clinical characteristics, preceding life problems and outcomes in individuals aged 60 years and over presenting to hospital following self‐harm. Method Data on Emergency Department (ED) presentations for self‐harm from 2003 to 2016 from three centres in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…Recent international studies have shown increases in rates in older adults aged 60 years and over presenting to hospitals with self-harm (Patel et al ., 2023). Internationally, rates of self-harm in older adults aged 60 years and over vary from 19 to 65 per 100,000 according to a systematic review (Troya et al ., 2019), with the most recent evidence showing increases in England 83.8 per 100,000 (Patel et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent international studies have shown increases in rates in older adults aged 60 years and over presenting to hospitals with self-harm (Patel et al ., 2023). Internationally, rates of self-harm in older adults aged 60 years and over vary from 19 to 65 per 100,000 according to a systematic review (Troya et al ., 2019), with the most recent evidence showing increases in England 83.8 per 100,000 (Patel et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Recent international studies have shown increases in rates in older adults aged 60 years and over presenting to hospitals with self-harm (Patel et al ., 2023). Internationally, rates of self-harm in older adults aged 60 years and over vary from 19 to 65 per 100,000 according to a systematic review (Troya et al ., 2019), with the most recent evidence showing increases in England 83.8 per 100,000 (Patel et al ., 2023). A previous Irish study calculated presentation rates for older adults aged 55 years and over from 2006 to 2008 (Corcoran et al ., 2010), with presentation rates of 83.4 per 100,000 in female presentations and 67.4 per 100,000 in male presentations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, Troya et al's (2023) study reminds us to not view older adults as one homogenous group. Mental and physical health concerns are commonly reported problems that precede self-harm in older adults (Morgan et al, 2018;Patel et al, 2023;Troya et al, 2019a), but gender comparisons have long shown differences in a multitude of other risk factors or precipitating problems, which may be equally important considerations for assessment and treatment (Hawton and Harriss, 2006).…”
mentioning
confidence: 99%
“…Some individuals are still regularly working and displaying characteristics closely aligned with a younger working age group, whereas others may be newly or several decades into retirement, and some experiencing significant deterioration in physical and/or mental health and cognitive function. Troya et al (2023), attempt to overcome some of these issues through their age subgroup analysis, adding to the existing knowledge of within group differences in the older adult population (Morgan et al, 2018;Murphy et al, 2012;Patel et al, 2023), which may provide important considerations for care provision.…”
mentioning
confidence: 99%